2014
DOI: 10.1007/s11033-014-3695-3
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of AtDREB1D transcription factor improves drought tolerance in soybean

Abstract: Drought is one of the major abiotic stresses that affect productivity in soybean (Glycine max L.) Several genes induced by drought stress include functional genes and regulatory transcription factors. The Arabidopsis thaliana DREB1D transcription factor driven by the constitutive and ABA-inducible promoters was introduced into soybean through Agrobacterium tumefaciens-mediated gene transfer. Several transgenic lines were generated and molecular analysis was performed to confirm transgene integration. Transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 48 publications
2
32
0
1
Order By: Relevance
“…DREB1, also known as CBF (C‐repeat binding factor), is responsible for cold tolerance (Gehan et al ., ). Recent research has indicated that DREB1D/CBF4 also enhances drought tolerance in plants (Haake et al ., ; Guttikonda et al ., ). However, the two DREB1Ds may not be the direct targets of GmWRKY54, as GmWRKY54 could not bind to their promoter regions.…”
Section: Discussionmentioning
confidence: 97%
“…DREB1, also known as CBF (C‐repeat binding factor), is responsible for cold tolerance (Gehan et al ., ). Recent research has indicated that DREB1D/CBF4 also enhances drought tolerance in plants (Haake et al ., ; Guttikonda et al ., ). However, the two DREB1Ds may not be the direct targets of GmWRKY54, as GmWRKY54 could not bind to their promoter regions.…”
Section: Discussionmentioning
confidence: 97%
“…For example, overexpression of DREB1A resulted in severe growth retardation under normal growing conditions (Guttikonda et al 2014). However, no adverse effects on growth and agronomic characteristics were found in transgenic PMI corn and wheat (Wright et al 2001;Negrotto et al 2000;Wang et al 2000), sugar beet (Joersbo et al 1998) and rice (Lucca et al 2001;He et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, leaf-related traits, such as stomata aperture and leaf cell membrane stability, have been also well-known traits that influence drought tolerance (Kaiser, 2009; Manavalan et al, 2009; Guttikonda et al, 2014; Ha et al, 2014). Overexpression of SNAC1 gene in rice was shown to enhance stomatal closure, thereby contributing to improved drought tolerance of transgenic plants (Hu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%